2020
DOI: 10.21608/atasu.2020.160431
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Operational Efficiency and Financial Performance on Capital Structure using Earnings Management as a Moderator Variable

Abstract: This research aims to investigate the association between operational efficiency and financial performance of the company on capital structure which is indicated in terms of the relative balance of the company financing sources using the earning management as a moderator variable in the process of management decision making regarding the enhancing the balance of the firm capital structure. We use a sample of 65 listed non-financial companies in the Egyptian Stock Exchange (EGX) during the 7 years (2013)(2014)(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…This implies that, after the mergers and acquisitions, the firms achieved optimal operating efficiency, enhanced revenue, improved capital base asset quality, and liquid asset. This outcome is similar to those of (Ranjan & Bishnu, 2017;Megeid et al, 2019;Natarajan et al, 2017). The findings were, however, inconsistent with other researchers who found an inverse relationship between operational efficiency and ROA Hongxing et al, 2018) other found no connection at all (Rania & Warrad ( 2015).…”
Section: Correlational Analysissupporting
confidence: 89%
“…This implies that, after the mergers and acquisitions, the firms achieved optimal operating efficiency, enhanced revenue, improved capital base asset quality, and liquid asset. This outcome is similar to those of (Ranjan & Bishnu, 2017;Megeid et al, 2019;Natarajan et al, 2017). The findings were, however, inconsistent with other researchers who found an inverse relationship between operational efficiency and ROA Hongxing et al, 2018) other found no connection at all (Rania & Warrad ( 2015).…”
Section: Correlational Analysissupporting
confidence: 89%